WHO Expert Committee on Specifications for Pharmaceutical Preparations : Forty-second Report. - WHO (Technical Report Series, No. 948., 2008)
The Expert Committee on Specifications for Pharmaceutical Preparations works towards clear, independent and practical standards and guidelines for medicines' quality assurance. Standards are developed by the Committee through worldwide consultation and an international consensus building process. The forty-second meeting adopted 11 new monographs for inclusion in The International Pharmacopoeia (Ph. Int.) and seven related new International Chemical Reference Standards (ICRS). The specifications currently developed are internationally applicable test methodologies for antimalarial, antitubercul.